Pembinaan Keagamaan Siswa Melalui Kegiatan Lembaga Dasar Kepemimpinan (LDK) - Muti'ah Muti'ah; Indah Muliati (An-Nuha, 2022)
This study aims to examine: 1) Implementation of religious development for students at SMAN 7 Padang through LDK activities 2) Supporting and inhibiting factors in the implementation of religious development for SMAN 7 Padang students through LDK activities. The method used by researchers in this study is qualitative with a descriptive approach. This research was conducted at SMAN 7 Padang. Data collection techniques used are observation, documentation and interviews. The data obtained from the study were then analyzed by data reduction, data presentation, and drawing conclusions. The data validity technique used is the triangulation technique, checking the data again with a different technique so as to get valid data. The results showed that 1) The purpose of holding LDK activities was to build the spirit of youth who were active and full of knowledge, Becoming a new generation with new enthusiasm, Introducing the ROHIS organizational structure and management structure, Training the leadership of ROHIS BIRU members at SMAN 7 Padang, Training ROHIS BIRU administrators SMAN 7 Padang to be able to organize well. 2) the basis for implementing LDK activities is by using the Qur'an and Sunnah. 3) The method used is discussion, lecture and habituation. 4) The coaching materials are faith, morals and worship. 5) Supporting and inhibiting factors for the implementation of religious development for SMAN 7 Padang students through LDK activities. Supporting factors: student enthusiasm, good cooperation, support from various parties and adequate facilities and infrastructure. Inhibiting factors: the occurrence of the covid-19 pandemic and the lack of openness among rohis administrators.